(untitled) (Lex Scientia Law Review, 2025)
In an era marked by the algorithmic mediation of human affairs, the pursuit of justice can no longer be disentangled from the architecture of digital systems that sustain it. The criminal justice system, long rooted in analog procedures and institutional inertia, faces an existential imperative: adapt or risk obsolescence. Within this context, digital transformation is not merely an administrative upgrade—it is a normative challenge to the principles of due process, transparency, and equality before the law. Indonesia’s hesitant transition toward e-criminal justice reveals a complex interplay of structural, legal, and epistemic limitations. This study aims to analyze the development of e-criminal justice in Indonesia by conducting a comparative assessment of successful digital judicial systems in the United States, the United Kingdom, and Singapore. Employing a normative legal research approach with a comparative legal method, this study examines primary and secondary legal sources to identify regulatory gaps, procedural challenges, and strategic solutions. The findings reveal that Indonesia’s legal framework remains insufficient in addressing key procedural safeguards, digital evidence authentication, and cybersecurity risks. Additionally, disparities in digital access, resistance from legal practitioners, and inadequate technological infrastructure hinder the effective implementation of e-criminal justice. Comparative analysis suggests that successful digital transformation requires a robust regulatory foundation, secure and interoperable digital platforms, structured judicial training programs, and policies ensuring digital inclusivity. To optimize its e-criminal justice framework, Indonesia must adopt a context-sensitive and adaptive strategy, balancing technological advancements with fundamental principles of procedural fairness and judicial integrity. Future research should explore the long-term impact of digitalization on judicial decision-making, the role of AI in legal processes, and the effectiveness of cybersecurity mechanisms in safeguarding judicial independence. This study contributes to the broader discourse on the intersection between technology and justice, providing recommendations for a sustainable and equitable digital transformation of Indonesia’s criminal justice system.